Biodiesel effects on particulate radiocarbon (C-14) emissions from a diesel engine - Bennett, Maren; Volckens, John; Stanglmaier, Rudy; McNichol, Ann P.; Ellenson, William D.; Lewis, Charles W. (JOURNAL OF AEROSOL SCIENCE, 2008)
The relative amount of C-14 in a sample of atmospheric particulate matter (PM), defined as percent modern carbon (pMC), allows the Environmental Protection Agency (EPA) to infer the fraction of PM derived from anthropogenic pollution sources. With increased use of biofuels that contain C-14, the main assumption of the two-source model, that C-14 is solely derived from biogenic emissions, may become invalid. The goal of this study was to determine the C-14 content of PM emitted from an off-highway diesel engine running on commercial grade biodiesel. Tests were conducted with an off-highway diesel engine running at 80% load fueled by various blends of soy-based biodiesel. A dilution tunnel was used to collect PM10 emissions on quartz filters that were analyzed for their C-14 content using accelerator mass spectrometry. A mobility particle sizer and 5-gas analyzer provided supporting information on the particle size distribution and gas-phase emissions. The pMC of PM10 aerosol increased linearly with the percentage of biodiesel present in the fuel. Therefore, PM emissions resulting from increased combustion of biodiesel fuels will likely affect contemporary C-14 apportionment efforts that attempt to split biogenic vs. anthropogenic emissions based on aerosol C-14 content. Increasing the biodiesel fuel content also reduced emissions of total hydrocarbons (THC), PM10 mass, and particulate elemental carbon. Biodiesel had variable results on oxides of nitrogen (NOx) emissions. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: biofuel; EC; OC; PM; source apportionment